2022
DOI: 10.3390/biomedicines10061379
|View full text |Cite
|
Sign up to set email alerts
|

Male Knock-in Mice Expressing an Arachidonic Acid Lipoxygenase 15B (Alox15B) with Humanized Reaction Specificity Are Prematurely Growth Arrested When Aging

Abstract: Mammalian arachidonic acid lipoxygenases (ALOXs) have been implicated in cell differentiation and in the pathogenesis of inflammation. The mouse genome involves seven functional Alox genes and the encoded enzymes share a high degree of amino acid conservation with their human orthologs. There are, however, functional differences between mouse and human ALOX orthologs. Human ALOX15B oxygenates arachidonic acid exclusively to its 15-hydroperoxy derivative (15S-HpETE), whereas 8S-HpETE is dominantly formed by mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(75 reference statements)
1
12
1
Order By: Relevance
“…Recently, these in vitro mutagenesis studies have been confirmed through the generation of Alox15b knock-in mice, in which the reported amino acids of Alox8 were substituted by those from human ALOX15B. As these humanized Alox15b knock-in mice formed only small amounts of 8-HETE, the substitution from Tyr 603 /His 604 in Alox8 towards Asp 602 /Val 603 in Alox15b confirms that these amino acid pairs are responsible for the different regiospecificity of the two enzymes ( Schäfer et al, 2022 ).…”
Section: Regiospecificity and Substrate Orientation Of Alox15b-cataly...mentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, these in vitro mutagenesis studies have been confirmed through the generation of Alox15b knock-in mice, in which the reported amino acids of Alox8 were substituted by those from human ALOX15B. As these humanized Alox15b knock-in mice formed only small amounts of 8-HETE, the substitution from Tyr 603 /His 604 in Alox8 towards Asp 602 /Val 603 in Alox15b confirms that these amino acid pairs are responsible for the different regiospecificity of the two enzymes ( Schäfer et al, 2022 ).…”
Section: Regiospecificity and Substrate Orientation Of Alox15b-cataly...mentioning
confidence: 80%
“…Recent data from Alox15b knock-in mice, humanized by mutation of the identified amino acid pair in Alox8, show that the hematopoietic system including erythrocyte number, hematocrit and hemoglobin is impaired in male mice. Also, this is paralleled by a premature growth arrest ( Schäfer et al, 2022 ). These mice provide a rare insight into the biological function of human ALOX15B and mouse Alox8 in vivo , as there are no commercially available Alox8-deficient mice to date.…”
Section: Introductionmentioning
confidence: 99%
“…The Alox15-KI mice characterized here were created in collaboration with Cyagen Bioscience (Santa Clara, USA). For this purpose, we employed a similar strategy that was used to humanize the reaction specificity of mouse Alox15b [ 23 ] but the protocol was adopted to mouse Alox15. The experimental details are explained in the Methodological Additional file 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Body weight kinetics of Alox15 -KI mice (either sex) and of wildtype controls ( n = 10) were quantified as described previously [ 23 ]. Statistic evaluation of the experimental raw data was performed using two-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation